2020
DOI: 10.1007/jhep04(2020)197
|View full text |Cite
|
Sign up to set email alerts
|

A light scalar explanation of (g − 2)μ and the KOTO anomaly

Abstract: The KOTO experiment has recently performed a search for neutral Kaons decaying into neutral pions and a pair of neutrinos. Three events were observed in the KOTO signal region, with an expected background of about 0.05. Since no clear signal of systematic errors have been found, the excess of events in the decay K L → π 0 νν is quite intriguing. One possibility to explain this anomaly would be the presence of a scalar φ with mass of the order of the pion mass and inducing decays K L → π 0 φ which mimic the obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 83 publications
(146 reference statements)
1
53
0
Order By: Relevance
“…Upon comparing with Ref. [16] we found that the choice p X ≈ 47 GeV fits best their simulation result and is also consistent with the result in Ref. [3].…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…Upon comparing with Ref. [16] we found that the choice p X ≈ 47 GeV fits best their simulation result and is also consistent with the result in Ref. [3].…”
Section: Introductionsupporting
confidence: 89%
“…(For other potential constraints, see discussions in Ref. [16].) We see that there is a small survival space for m X < 60 GeV, i.e., with m X ∈ ð45; 60Þ MeV and τ X ∈ ð0.04; 0.11Þ ns.…”
Section: And the Upper Bound Onmentioning
confidence: 79%
See 2 more Smart Citations
“…Finally, the NP models of refs. [12,[14][15][16][17][18][19][20][21] do not violate the GN bound, but can allow for a large signal in KOTO since NA62 is not sensitive to X inv with a mass close to the pion mass.…”
Section: Jhep07(2020)229mentioning
confidence: 99%